Characterization of a stearoyl-acyl carrier protein desaturase gene family from chocolate tree, Theobroma cacao L - Zhang, Yufan; Maximova, Siela N.; Guiltinan, Mark J. (Frontiers in Plant Science, 2015)
In plants, the conversion of stearoyl-ACP to oleoyol-ACP is catalyzed by a plastid-localized soluble stearoyl-acyl carrier protein (ACP) desaturase (SAD). The activity of SAD significantly impacts the ratio of saturated and unsaturated fatty acids, and is thus a major determinant of fatty acid composition. The cacao genome contains eight putative SAD isoforms with high amino acid sequence similarities and functional domain conservation with SAD genes from other species. Sequence variation in known functional domains between different SAD family members suggested that these eight SAD isoforms might have distinct functions in plant development, a hypothesis supported by their diverse expression patterns in various cacao tissues. Notably, TcSAD1 is universally expressed across all the tissues, and its expression pattern in seeds is highly correlated with the dramatic change in fatty acid composition during seed maturation. Interestingly, TcSAD3 and TcSAD4 appear to be exclusively and highly expressed in flowers, functions of which remain unknown. To test the function of TcSAD1 in vivo, transgenic complementation of the Arabidopsis ssi2 mutant was performed, demonstrating that TcSAD1 successfully rescued all AtSSI2 related phenotypes further supporting the functional orthology between these two genes. The identification of the major SAD gene responsible for cocoa butter biosynthesis provides new strategies for screening for novel genotypes with desirable fatty acid compositions, and for use in breeding programs to help pyramid genes for quality and other traits such as disease resistance.